Navigating the terrain of teenage pregnancy: a socio-demographic and health outcomes study focused on contraceptive knowledge, attitudes, and practices among urban adolescents - Fotedar, Nidhi; Masthi, N. R. Ramesh; Lakshminarayana, Sanjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Teenage pregnancy remains a significant public health concern in India, with far-reaching implications for maternal and child health. This study aims to examine the socio-demographic profiles, pregnancy outcomes, and contraceptive knowledge, attitudes, and practices (KAP) among urban adolescents in Bangalore. Methods: This hybrid study combined retrospective analysis of 707 antenatal records and prospective follow-up of 62 pregnant teenagers (aged <19 years) at an urban referral hospital in Bangalore between August 2021 and January 2022. A structured questionnaire assessed contraceptive KAP via telephone interviews. Results: Most participants were 19 years old (82.3%) and from Bangalore Urban (77.4%). While 62.9% had heard about contraceptives, only 35.5% reported ever using them. Condoms (48.8%) and birth control pills (38.8%) were the most known methods. Media (44.6%) and healthcare professionals (43.1%) were primary information sources. Attitudes towards contraceptives were largely neutral (80.6%). Partner's refusal (40%) and lack of knowledge (37.6%) were main reasons for non-use. Education was significantly associated with contraceptive knowledge (p=0.022), while the source of information was associated with attitudes (p=0.032). Conclusions: This study reveals significant gaps in contraceptive knowledge and practices among urban adolescents in Bangalore. Findings highlight the need for comprehensive sexuality education, improved access to youth-friendly reproductive health services, and interventions addressing gender dynamics in contraceptive decision-making. These insights contribute to understanding adolescent reproductive health in urban India and call for multifaceted strategies to reduce teenage pregnancy rates and improve reproductive health outcomes.